Rekonstruksi Pendidikan Berbasis Dakwah Entrepreneurship di Pondok Pesantren Nurul Haramain Narmada dalam Dimensi Al Qur'an - Udin, (TADRIS: Jurnal Pendidikan Islam, 2021)
Humans are given the power to navigate this nature so that they can benefit from this natural wealth such as by cultivating tilapia. Not only fish farming, humans can get results, but also with trade or commerce which for the students of the Nurul Haramain Narmada Islamic boarding school by forming a boarding school cooperative, and cultivating agricultural land, so that entrepreneurship or entrepreneurship has a positive impact on the students of the Nurul Haraimain Islamic boarding school and has positive implications for the surrounding community. God has bestowed various favors, besides humans being able to enjoy natural resources, the produce of the earth can also be used as a means of connecting between regions. This is how God bestows on humans to worship Him and achieve prosperity in life. The use of natural resources discussed in the Qur'an is a form of depiction of entrepreneurs or entrepreneurs as achieving balance in human life in the world and the hereafter, therefore entrepreneurship-based education is very important to be practiced, especially in the Nurul Haramain Narmada Islamic boarding school and it turns out that entrepreneurship-based education have a positive impact both among students and the surrounding community.